Wireless Landmines Tracking System Based on GPS and GPRS - Khalifa, SSM; Saadan, K; Norwawi, NM (IEEE, 2024)
One of the most challenges facing the developing countries and standing in the way of their growth are remnants of war and landmines. These countries have inherited this legacy during the World War I and II which represents a major threat to lives. Furthermore, it hinders reconstruction and development efforts. The aim of this research is to find a low cost alternative for protecting and warning people about landmines risk during practicing their daily lives. In this context, this paper presented the design and development of a Wireless Landmines Tracking System (WLTS) using smart phone. The Android software development kit (SDK) has been used to develop this system. This system is really very helpful for the users who live near mine affected areas to track their children and themselves through mobile phones from landmines risk.